PELAKSANAAN PEMENUHAN KEWAJIBAN PAJAK RESTORAN OLEH RESTORAN LAPO NI TONDONGTA PADA TAHUN 2014 - Surnamin Surnamin; Toni Triyulianto; Iis Susanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2015)
.Lapo Ni Tondongta Restaurant as a Domestic Taxpayer is obliged to fulfill restaurant tax obligations in 2014. In fulfilling these obligations, Lapo Ni Tondongta Restaurant performs Restaurant Tax obligations not in accordance with the applicable tax regulations in the case of the Restaurant Tax Law with reference to Provincial Regulation DKI Jakarta No. 11 of 2011. The purpose of this study is to determine whether the implementation of fulfillment of the obligation to collect, calculate, deposit and report on restaurant tax by Lapo Ni Tondongta Restaurant is in accordance with the applicable tax regulations. In collecting this Final Project Report data the authors make observations, interviews and citation of documents as supporting authors in order to get complete, accurate and valid data. It was concluded that in the implementation of Collection, Calculation, Depositing and Restaurant Tax Reporting by Lapo Ni Tondongta Restaurant in 2014 it was in accordance with the applicable tax regulations.